P 36 Structural and functional imaging findings in somatoparaphrenia. Issue 10 (October 2017) - Schmitz-Peiffer, H.; Krukowski, P.; Hallmeyer-Elgner, S.; Pinzer, T.; Schackert, G.; Reichmann, H.; Kitzler, H.
Abstract : Background: With regard to somatosensory delusion, neglect or deficits of body integrity a great number of overlapping pathophysiological concepts exist. Moreover, the range of assumed underlying psychiatric and neurologic syndromes only partially is thought to be related to even diverse neuroanatomical structures so far: Alien Hand Syndrome, Body Dysmorphic Disorder (BDD), Body Integrity Identity Disorder (BIID), Depersonalization, Somatoparaphrenia and Xenomelia. Specific deafferentiation within temporal regions, the insula or representational structures of the somatosensory cortex of the right parietal lobe is thought to be related only in some variants. We report a case of a 58-year old right-handed woman that experienced a progressive left-sided hemiparesis which initially could be related to a space occupying lesion and edema in the right central region of the brain. After anti-edematous therapy and consecutive surgical evacuation a cortical and subcortical defect in between the right postcentral gyrus junction to the precentral gyrus resulted into inanimate, not inherent sensations especially of the left forearm and knee without anosognosia after complete recovery of motor function and sensitivity. The neuropsychological assessment showed no impairments. Methods: We demonstrate structural (conventional MRI) and functional imaging findings (diffusion tensor imaging; DTI, and, motor and somatosensory functional MRI) in relation to the subject"s somatosensory delusions. Results: Structural MRI displayed a well-defined cortical and subcortical lesion in deep central sulcus surrounded by gliosis and hemosiderin deposits. DTI revealed a marked reduction of structural inter-connection between precentral and postcentral gyrus. In fMRI the motor paradigm series of dorsal flexion of the feet or clenching the fists showed no difference in activation of the correspondent precentral gyrus. The sensor paradigm series in contrast revealed a lower posterior activation of the right postcentral area during brushing the planta pedis and the left forearm. Discussion: The hereby presented case possesses rare clinically segregated symptoms of somatoparaphrenia without anosognosia or hemiparesis in conjunction with a well-defined postcentral lesion. The symptoms may be related to a corresponding reduced postcentral activation and restricted functional interconnection between motor and sensory cortex. From our point of view these results document the essential requirement of postcentral gyrus activation and regional conduction for regular experience of sensorial authenticity.